'Let's do some jumping together': Intergenerational participation in the use of remote technology to co-construct social relations over distance. (February 2015) - Kelly, Clare
This article discusses a small-scale study that explores how members of one family based in Australia and the United Kingdom use remote technology to develop and maintain family relationships across generations and distance. Of particular interest was the manner in which Skype computer software was mediated to develop intersubjectivity between a 4-year-old girl and her grandparents. Encounters were filmed, transcribed and coded; participants were interviewed and asked to keep reflective diaries. Analysis showed that all the adults scaffolded the child's interactions to sustain communication and help her negotiate meaning with her grandparents as virtual partners, but that she also took on a leadership role by appropriating the affordances of the medium to incorporate them in her play in creative ways.